BANK EFFICIENCY AND FINTECH-BASED INCLUSIVE FINANCE: EVIDENCE FROM DUAL BANKING SYSTEM - Hasanul Banna; M Kabir Hassan; Hassan Bataineh (Bank Indonesia, 2023)
This paper examines the relation between fintech-based inclusive finance and bank efficiency using annual unbalanced data of 318 banks from 7 dual-banking countries over the period of 2011 to 2020. It measures bank efficiency using the data envelopment analysis (DEA) and then applies the Simar-Wilson bootstrapping regression to measure the influence of fintech-based financial inclusion on bank efficiency. From the efficiency measures, we note that Islamic banks are more efficient than their conventional counterparts. Our regression analysis indicates that fintech-based inclusive finance is positively related to bank efficiency, implying that greater implementation of digitally integrated financial system improves banking efficiency. Our findings are robust in alternative estimation methods. Our study provides some policy implications for policymakers, standard setters, and regulators.